Urban B40 secondary school student creativity versus their rural counterparts - Marzuki, Ibrahim; Imran, Abdullah; Mohd Hisham, Omar; Sheikh Ahmad Tajuddin, Sh. Yusoff; Muhammad Afiq, Yahyaawal (2021)
Creativity is an important asset to our nation Malaysia as the need for "creative"workforce is increasing. In a report by Sinar Harian, Malaysia was ranked 35th in the Global Innovation Index (GII) and resides among middle income countries endeavouring to close the innovation gap. Following this fact, this research was proposed with the main objective of identifying real creativity level of B40 Malaysian students. The research instrument was a questionnaire modified according to Torrance Creative Thinking Test, where its Verbal Test and Figural Test were fashioned to measure creativity based on the four measuring indexes proposed by Yong, namely Originality, Fluency, Flexibility, and Elaboration. Datas procured were analyzed via descriptive statistics; from it several creativity aspect suggestions that could be implemented in Malaysia were brought forward. The findings of this research can be leveraged by stakeholders when planning the social system, education, work, economy, and improving Malaysia's standings in the Global Creativity and Global Creative Class indexes to similar heights as other Asia Pasific countries.